2020
DOI: 10.5194/hess-24-5919-2020
|View full text |Cite
|
Sign up to set email alerts
|

Diverging hydrological drought traits over Europe with global warming

Abstract: Abstract. Climate change is anticipated to alter the demand and supply of water at the earth's surface. Since many societal impacts from a lack of water happen under drought conditions, it is important to understand how droughts may develop with climate change. This study shows how hydrological droughts will change across Europe with increasing global warming levels (GWLs of 1.5, 2, and 3 K above pre-industrial temperature). We employed a low-flow analysis based on river discharge simulations of the LISFLOOD (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 63 publications
1
13
0
Order By: Relevance
“…Besides, the stationary assumption is made within a given time window (typically 30 years) for the historical and future climate in most of the drought projection studies (Cammalleri et al, 2020;Gu, Chen, Yin, Sullivan, et al, 2020;Naumann et al, 2018). However, the stationarity assumption for the future period is challenged in the global warming context, especially when a long time period is selected Jehanzaib et al, 2020;Mukherjee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides, the stationary assumption is made within a given time window (typically 30 years) for the historical and future climate in most of the drought projection studies (Cammalleri et al, 2020;Gu, Chen, Yin, Sullivan, et al, 2020;Naumann et al, 2018). However, the stationarity assumption for the future period is challenged in the global warming context, especially when a long time period is selected Jehanzaib et al, 2020;Mukherjee et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…They found that drought risks are projected to increase significantly for warming levels in the Mediterranean, central Europe, the Amazon, southern Africa, and Southern Australia relative to the present-day reference period . Cammalleri et al (2020) investigated the changes in hydrological droughts over Europe under 1.5, 2, and 3°C warming levels, and they found an opposite tendency in the Mediterranean and Boreal sub-regions of Europe in warmer climates. Specifically, the former region is projected to suffer an exacerbated drought condition with the temperature rising, while that in the latter region will be relieved.…”
Section: Projected Changes In Meteorological and Hydrological Drought...mentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in water consumption may even be of the same magnitude as the projected impact of climate change [35]. Meanwhile, according to Cammalleri et al [36], the projected increases in water demand may play a more critical role in the future than climate change in continental subregions of Europe. In the dry Mediterranean climate, projections indicate that flows are probably lower in all months of the year.…”
Section: Introductionmentioning
confidence: 99%